Varieties of Impact Investing: Creating and Translating a Label in Local Contexts - Balsiger, Philip; Burnier, Daniel; Kabouche, Noé (Business, Finance and International Development, 2025)
Available open access digitally under CC-BY-NC-ND licence. A new trend in ethical finance, impact investing aims to generate positive social or environmental impacts alongside financial returns. But what does it really mean and how is it practiced across different regions and organizations? This volume explores the malleability of impact investing and how it overlaps with the development sphere to give finance a new role. From global networks to the Global South, it compares diverse investing practices and discourses. Providing an original perspective on this emerging field, this is a key resource for the scholars of social studies of finance, economic sociology, management and organization studies.